17th Latest Advances in Psychiatry Symposium 2018. Issue 3 (22nd August 2018) - David, Felix
Abstract : The 2018 Latest Advances in Psychiatry Symposium was held in March at the Royal College of Physicians, London, with the theme 'causes, correlates and consequences of mental ill health'. Here, Felix David covers highlights on perinatal guidelines, inflammation and depression, and the association between proteostasis and schizophrenia.